Urinary excretion of 9α,11β-prostaglandin F2 and leukotriene E4 in patients with exercise-induced bronchoconstriction - Shin, Tae-Rim; Kim, Joo-Hee; Kim, Cheol-Hong; Hyun, In-Gyu; Choi, Jeong-Hee (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Background: Increased levels of mast cell-derived eicosanoids, such as prostaglandin (PG) D2 and cysteinyl leukotrienes (CysLTs), have been reported in patients with exercise-induced bronchoconstriction (EIB), suggesting that mast cell activation is involved in the mechanism of EIB. However, it is still controversial since these results have not been reproduced in other studies. The aim of this study was to evaluate the role of PGD2 and LTE4 in adult asthma with EIB, as measuring urinary levels of their metabolites—9α,11β-PGF2 and LTE4 before and after an exercise challenge test. Methods: Eight patients with asthma and EIB and five normal controls without EIB were enrolled. Exercise challenge tests comprised of 6 min of treadmill exercise or free running were performed in all study subjects, and urine samples before and 1 h after the challenge were collected. Urinary levels of 9α,11β-PGF2 and LTE4 were measured by enzyme immunoassay (EIA). Results: No significant differences were observed in 9α,11β-PGF2 and LTE4 levels before/after the exercise challenge between patients with EIB and normal controls. No significant increases in urinary levels of 9α,11β-PGF2 or LTE4 were detected during the exercise challenge in patients with EIB and normal controls. No significant correlations were observed between the percent decrease in forced expiratory volume in 1 s (FEV1) or percent changes in 9α,11β-PGF2 and LTE4 levels after the exercise challenge. Conclusions: Urinary 9α,11β-PGF2 and LTE4 levels did not increase after an exercise challenge in patients with EIB, suggesting that urinary excretion of 9α,11β-PGF2 and LTE4 may not be a good marker of mast cell activation in patients with EIB.